No antibiotics in acute uncomplicated diverticulitis: does it work?. (December 2014) - Isacson, Daniel; Andreasson, Kalle; Nikberg, Maziar; Smedh, Kenneth; Chabok, Abbas
Abstract Background. The first randomized multicenter study evaluating the need for antibiotic treatment in patients with acute uncomplicated diverticulitis (AUD) could not demonstrate any benefit gained from antibiotic use. The aim of this study was to review the application of the no antibiotic policy and its consequences in regard to complications and recurrence. Methods. This retrospective population-based cohort study included all patients diagnosed with all types of colonic diverticulitis during the year 2011 at Västmanland Hospital Västerås, Sweden. All medical records were carefully reviewed. Primary outcomes were the types of treatment adopted for diverticulitis, complications and recurrence. Results. In total, 246 patients with computer tomography-verified diverticulitis were identified, 195 with primary AUD and 51 with acute complicated diverticulitis. Age, sex, and temperature at admission were similar between the groups but there was a significant difference in white blood cell count, C-reactive protein, and length of hospital stay. In the AUD group, 178 (91.3%) patients were not treated with antibiotics. In this group, there were six (3.4%) readmissions but only two developed an abscess. Of the remaining 17 patients (8.7%) who were treated with antibiotics in the AUD group, one developed an abscess. Twenty-five (12.8%) patients in the AUD group presented with a recurrence within 1 year. Conclusion. The no-antibiotic policy for AUD is safe and applicable in clinical practice. The previous results of a low complication and recurrence rate in AUD are confirmed. There is no need for antibiotic treatment for AUD. What does this paper add to the literature? Despite published papers with excellent results, there are still doubts about patient safety against the policy to not use antibiotics in acute uncomplicated diverticulitis. This is the first paper, in actual clinical practice, to confirm that the no antibiotic policy for acute uncomplicated diverticulitis is applicable and safe.